Music as a Medium of Liturgy, Spirituality, and Cultural Identity: A Study of Worship in GMIM: Musik sebagai Medium Liturgi, Spiritualitas, dan Identitas Budaya: Studi tentang Ibadah di GMIM - Novyanty Pricilia Purnama; Zhally Yacoba Mambrasar; Moses Abraham Milton Rundubelo; Theofilus Josua Turangan; Villya Indriani Laleno; Denny Adry Tarumingi; Mieke Nova Sendow; Evi Stans Evlin Tumiwa (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study examines the role of music in the worship of Gereja Masehi Injili di Minahasa (GMIM) as a locus where liturgy, spirituality, and cultural identity intersect. Using a qualitative case study design, data were collected through participant observation, semi-structured interviews with worship leaders, music ministers, and congregants, and an analysis of liturgical documents and song repertoires. The thematic analysis identified three major findings. First, GMIM worship is characterised by a dynamic interplay between contemporary Christian music, hymns, and traditional Minahasan forms, which together structure the liturgical flow from joyful praise to prayerful contemplation. Second, music functions as a primary medium of spiritual experience, helping congregants focus on God, articulate complex emotions, and internalise theological themes, while also revealing the risks of distraction when musical practices become performance-centred or misaligned with the liturgy. Third, congregational participation is shaped by the leadership of worship leaders and musicians, whose technical competence, spiritual maturity, and cultural sensitivity facilitate intergenerational engagement, despite differing musical preferences. The study concludes that music in GMIM worship is not a peripheral ornament but a vital aspect of pastoral ministry, theological formation, and inculturation. It recommends training for music ministers, intentional integration of traditional and contemporary repertoires, and participatory worship planning to ensure that GMIM worship remains contextually rooted and responsive to contemporary challenges.